Cupric Nitrate Catalyzed Efficient and Facile Synthesis of 1,8-Dioxo-octahydroxanthene Derivatives - Nasreen, Aayesha (Asian Journal of Chemistry, 2013)
An efficient and convenient approach to the synthesis of 1,8-dioxo-octahydroxanthene derivatives by using catalytic amount (10 mol %) of cupric nitrate [Cu(NO3)2·3H2O] in acetonitrile and the yields obtained are in good to excellent (75-96 %). The reaction is highly chemo selective and applicable to aldehydes only.